Endaural extracranial repair for cerebrospinal otorrhoea with human fibrin glue: technical note. Issue 11 (November 1988) - Ferrante, L; Palatinsky, E; Acqui, M; Mastronardi, L
Abstract : A simple surgical procedure for the repair of cerebrospinal otorrhoea using human fibrin glue has proved safe and successful in two patients with post-surgical fistula. The procedure, which requires only mild sedation, is recommended for open or closed cerebrospinal otorrhoea accompanied by severe neurosensory hearing loss, as long as the fistula has not been caused by chronic inflammatory processes or given rise to intracranial infectious complications.